2020
DOI: 10.3389/fcell.2020.578036
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression Profiling Reveals Isorhamnetin Induces Hepatic-Lineage Specific Differentiation in Human Amniotic Epithelial Cells

Abstract: Isorhamnetin Induces Hepatic-lineage-Specific Differentiation in hAEC evident by significant downregulation of several colon-and cholangiocyte-specific markers. However, longer treatment with isorhamnetin did not promote hepatic maturation. Altogether, our findings indicate that isorhamnetin has a promising effect on directing the hepatic-lineage specific differentiation in hAECs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Natural bioactive compounds have great potential to induce the targeted differentiation of stem cells in a lineage-specific manner by modulating cellular behavior and early biological and molecular events; however, only a handful of studies explored it. In our previous studies, we have reported that a caffeic acid ester (rosmarinic acid), a caffeoylquinic acid derivative (TCQA), and an iridoid glycoside (verbenalin) directed the differentiation of hAECs towards neuronal-lineage, whereas a flavonol aglycone isorhamnetin induced hepatic-lineage specific differentiation in hAECs [ 8 , 9 , 10 , 11 ]. We assume that other compounds from the anthocyanin group may have a similar effect as Cy3G on hAEC’s fate choice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural bioactive compounds have great potential to induce the targeted differentiation of stem cells in a lineage-specific manner by modulating cellular behavior and early biological and molecular events; however, only a handful of studies explored it. In our previous studies, we have reported that a caffeic acid ester (rosmarinic acid), a caffeoylquinic acid derivative (TCQA), and an iridoid glycoside (verbenalin) directed the differentiation of hAECs towards neuronal-lineage, whereas a flavonol aglycone isorhamnetin induced hepatic-lineage specific differentiation in hAECs [ 8 , 9 , 10 , 11 ]. We assume that other compounds from the anthocyanin group may have a similar effect as Cy3G on hAEC’s fate choice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have reported that verbenalin, a kind of phytochemical, has exerted therapeutic potential for Alzheimer's disease in hAECs [8]. Microarray gene expression profiling showed that rosmarinic acid-and isorhamnetintreated hAECs exerted neuronal and hepatic-lineage specific differentiation potential respectively [9,10]. A caffeoylquinic acid derivative, namely 3,4,5-Tri-O-Caffeoylquinic Acid, has also enhanced neural and pigment cell differentiation in hAECs [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of plant-based natural products that may affect the differentiation of stem cells has been approved in the mainstream of medicine because of their high availability, minimum toxicity, and low secondary effects [ 16 , 17 ]. It has been reported that different natural compounds may regulate early biological events in hAECs to induce directed differentiation such as rosmarinic acid induced neuronal differentiation, whereas isorhamnetin induced hepatic-lineage specific differentiation in hAECs [ 18 , 19 ]. Also, verbenalin-treated hAECs revealed a therapeutic potential for Alzheimer’s disease [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, because of its stem cell-like properties, it can be used for the initial screening of target compounds. We have previously explored antifibrotic [ 71 ] and hepatic differentiation-inducing [ 170 ] potential of isorhamnetin in hAECs. In the present study, we have performed a targeted secondary analysis of our previously published data [ 71 ] to explore the potential functionalities of isorhamnetin in diabetes ( Figure 4 ).…”
Section: A Post Hoc Transcriptome Analysis Predicts the Potential Effect Of The Isorhamnetin On Diabetes In A Stem Cell-based Toolmentioning
confidence: 99%
“…A total of 303 DEGs were identified; among them, 60 were upregulated and 243 were downregulated. Details of methodology have been explained elsewhere [ 71 , 170 ]. All microarray data are available at Gene Expression Omnibus (GEO) under accession number: GSE153149 ( , accessed on 24 November 2021).…”
Section: A Post Hoc Transcriptome Analysis Predicts the Potential Effect Of The Isorhamnetin On Diabetes In A Stem Cell-based Toolmentioning
confidence: 99%